Dry Transportation of Sea Bass Using Clove Oil - Megi Rosmiati Mbuilima; Yuliana Salosso; Ade Yulita Hesti Lukas (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
White sea bass (Lates calcarifer) is a valuable fishery commodity that holds a significant market share, including as an export product. The high demand for white sea bass necessitates its seamless transportation. However, most fish experience stress to the point of death during transportation, and accommodations are expensive. Therefore, dry system transportation is a method that has the potential to be applied to reduce fish stress and lower transportation costs. This research was conducted using a completely randomized design (CRD) with three treatments and three replications, utilizing white snapper seeds measuring 5-6 cm. The treatments tested had different densities, specifically treatment A with 10 individuals, treatment B with 15 individuals, and treatment C with 20 individuals. Fish transportation was carried out with previous fish anesthesia, using commercial clove oil as an anesthetic at a dose of 0.10 ml/L of seawater. Based on observations of transportation during the 1-hour journey, treatment C with a density of 20 animals was the best , namely with an inductive time of 4 minutes, a stun time of 1 hour, and a sedative time of 18 minutes, resulting in a post-transportation survival rate of 78% and a post-rearing survival rate of 76%. The use of clove oil was effective in maintaining the survival rate of white snapper (Lates calcarifer) seeds after dry transportation and throughout the research period.